Menggali Nilai Humanisme dalam Cerpen Pilihan Kompas: Perspektif Pendidikan dan Sosial - Junyanti, Eny; Harjito, Harjito; Asrofah, Asrofah (Jurnal Prakarsa Paedagogia, 2024)
Navigating Human Essence: Interpretive Landscapes in Contemporary Indonesian Short Fiction. This research delves into the intricate tapestry of human experiences embedded within seven contemporary Indonesian short stories, exploring how narrative architectures reveal nuanced sociocultural dynamics. Utilizing an innovative qualitative hermeneutic methodology, the study deconstructs literary representations of human interactions beyond conventional narrative frameworks. The investigation unveils multilayered expressions of existential struggles, highlighting how literary texts function as critical social dialogues. By examining character trajectories, relational complexities, and embedded cultural narratives, the research illuminates subtle mechanisms of human resilience, empathy, and transformative potential. Findings suggest that literary texts serve as profound anthropological documents, capturing the intricate negotiations of identity, moral consciousness, and social adaptation in rapidly changing Indonesian societal contexts.